Regression of Liver Fibrosis - Campana, Lara; Iredale, John P. (Seminars in Liver Disease, 2017)
Liver fibrosis is the final common pathway of chronic or iterative liver damage. Advanced chronic fibrosis is described as cirrhosis with a loss of architecture and attendant functional failure and the development of life-threatening complications. However, compelling evidence from rodent models and human studies indicates that if the injury is removed liver fibrosis is reversible. Hepatocytes, activated hepatic stellate cells, endothelial and immune cells, particularly macrophages, cooperate in the establishment and resolution of liver fibrosis. Here the authors provide a short overview of the mechanisms regulating the profibrotic and proresolution response, with the aim of highlighting potential new therapeutic targets. Liver disease is a major unmet medical need; currently, the sole approaches are the withdrawal of the injurious stimulus and liver transplantation. The authors conclude with a brief review of the feasibility of macrophage-based cell therapy for liver fibrosis.
Keywords: liver; fibrosis; metalloproteases; macrophages; hepatic stellate cells